Challenges and opportunities in paediatric cardiac services: Time for action - Zühlke, Liesl (SA Heart Journal, 2017)
The 6th World Congress of Paediatric Cardiology and Cardiac Surgery recently held in Cape Town attracted over 3 000 registered delegates, the vast majority of which were scientific attendees. This congress, hosted by the South African Heart Association and organised by the Paediatric Cardiac Society of South Africa, highlighted the needs of children and adults with highly complex congenital cardiac lesions as well as those with acquired preventable disease such as rheumatic heart disease and noncommunicable cardiovascular diseases with their origins in childhood. The scientific programme addressed the most recent advances in paediatric cardiac disease and reflected new developments in treatment, diagnosis and management while constantly reminding delegates of inadequacies, inequalities and health system concerns affecting patient care.